The Effectiveness of Think-Talk-Write Technique to Teach Writing to Students with Different Personalities - Prestika , Aulfa Reyza Ayuni (Yayasan Kyadiren, 2023)
This research analyzed the effectiveness of Think-Talk-Write (TTW) and Fact-Reason-Elaboration-Shift (FRESH) techniques for teaching writing to students with extroverted and introverted personalities. A quantitative and 2 x 2 factorial research design involved 60 eighth-grade students. Three instruments—a personality questionnaire, observation checklist, and writing test—collected data. Both TTW and FRESH techniques positively impacted the writing abilities of extroverted and introverted students, with TTW showing stronger improvement. Individual characteristics must be considered when selecting teaching techniques. The findings provide evidence of effective writing instruction for different personality types, emphasizing the need for tailored approaches. Future research should explore additional techniques and factors to enhance our understanding of effective writing instruction.